2023
DOI: 10.3389/fnut.2023.1154409
|View full text |Cite
|
Sign up to set email alerts
|

Association of prognostic nutritional index with risk of contrast induced nephropathy: A meta-analysis

Abstract: BackgroundAlthough prognostic nutritional index (PNI) has been frequently applied in patients with malignancy or those during postoperative recovery, whether it is also an optimal indicator of the risk of contrast-induced nephropathy (CIN) in patients receiving coronary angiography remains uncertain. This meta-analysis aimed at investigating the clinical association of PNI with the risk of CIN in patients receiving coronary angiography or percutaneous coronary intervention.MethodsEmbase, Medline, Cochrane Libr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…To our knowledge, this is the first study to examine the correlation between malnutrition and the risk of acute kidney injury (AKI) from a global perspective. Although previous studies have deepened our understanding of the relationship between malnutrition and contrast-induced nephropathy [ 54 ], it is crucial to note that contrast-induced nephropathy and AKI are two different pathologies with distinct etiologies, pathophysiological mechanisms, and clinical presentations. In our research, we focus on the association between malnutrition and AKI.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study to examine the correlation between malnutrition and the risk of acute kidney injury (AKI) from a global perspective. Although previous studies have deepened our understanding of the relationship between malnutrition and contrast-induced nephropathy [ 54 ], it is crucial to note that contrast-induced nephropathy and AKI are two different pathologies with distinct etiologies, pathophysiological mechanisms, and clinical presentations. In our research, we focus on the association between malnutrition and AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the TyG index, a recent meta-analysis of four studies involving 1346 patients found that gamma-glutamyl transferase (GGT) levels could potentially predict CIN in patients undergoing cardiac catheterization, showing a significantly higher GGT levels in patients with CIN (odds ratio: 3.21; I 2 :91.93%) (27). In our previous meta-analysis, patients with a low prognostic nutritional index (PNI) demonstrated a higher risk of CIN than those with a high PNI, with an odds ratio of 3.362 (I 2 = 89.6%) (28). Although both GGT levels and PNI appear to have a stronger relationship with CIN than the TyG index, the relatively low heterogeneity in the current meta-analysis highlighted that the TyG index may be a reliable predictor of CIN.…”
Section: Discussionmentioning
confidence: 99%